The Herd-Level Sensitivity of Abattoir Surveillance for Bovine Tuberculosis: Simulating the Effects of Current and Potentially Modified Meat Inspection Procedures in Irish Cattle - Willeberg, Preben W.; McAloon, Conor G.; Houtsma, Erik; Higgins, Isabella; Clegg, Tracy Ann; More, Simon J. (Frontiers in Veterinary Science, 2018)
The European Food Safety Authority (EFSA) has published a series of opinions to assess the impact of changing from the current meat inspection procedures (CMI) to visual-only inspection (VOI) procedures. Concern has been raised that changes from CMI to VOI would adversely affect the effectiveness of surveillance for bovine tuberculosis (bTB) in EU member states, both for countries with and without official status of bTB freedom (OTF and non-OTF countries, respectively). This study was conducted to estimate the impact of a change from CMI to VOI in abattoirs on herd-level detection sensitivity in Ireland, a non-OTF country. Using national Irish data, we identified all herds that sold at least one animal to slaughter during 2010-12 whilst unrestricted for bTB. For each of these herds, we calculated the number of cattle sent to slaughter whilst unrestricted, the number of factory lesion tests (FLT) that had been performed, and estimated the apparent within-herd prevalence (APwh). A FLT is a whole-herd test conducted in a herd following the confirmation of bTB in an animal at slaughter. We considered five different inspection scenarios, each based on meat inspection and bacteriology in series, including current meat inspection (CMI) and four visual-only inspection scenarios (VOI2, VOI3, VOI4, VOI5) with reducing inspection sensitivities. Separately for each inspection scenario, a simulation model was used to estimate the herd-level detection sensitivity and the number of bTB-herds (that is, herds that sent at least one animal detected with M. bovis to slaughter when unrestricted during 2010-12) that would and would not be detected. The simulated mean herd-sensitivity estimates were 0.24 for CMI, and 0.16, 0.12, 0.10 and 0.08 for VOI2-5, assuming a 2-, 3-, 4- and 5-fold decrease, respectively, in the animal-level detection sensitivity of VOI relative to that of CMI. The estimated number of non-detected bTB-herds is substantial with CMI, and increases in the series of VOI scenarios with decreasing herd-level sensitivity. If VOI were introduced without alternative surveillance means to compensate for the decrease in abattoir inspection sensitivity, such changes might jeopardise bTB surveillance, control and eradication programmes in cattle herds of non-OTF countries, including Ireland.